Acute and training effects of resistance exercise on heart rate variability - Kingsley, J. Derek; Figueroa, Arturo (Clinical physiology and functional imaging, 2016)
Summary Heart rate variability (HRV) has been used as a non‐invasive method to evaluate heart rate (HR) regulation by the parasympathetic and sympathetic divisions of the autonomic nervous system. In this review, we discuss the effect of resistance exercise both acutely and after training on HRV in healthy individuals and in those with diseases characterized by autonomic dysfunction, such as hypertension and fibromyalgia. HR recovery after exercise is influenced by parasympathetic reactivation and sympathetic recovery to resting levels. Therefore, examination of HRV in response to acute exercise yields valuable insight into autonomic cardiovascular modulation and possible underlying risk for disease. Acute resistance exercise has shown to decrease cardiac parasympathetic modulation more than aerobic exercise in young healthy adults suggesting an increased risk for cardiovascular dysfunction after resistance exercise. Resistance exercise training appears to have no effect on resting HRV in healthy young adults, while it may improve parasympathetic modulation in middle‐aged adults with autonomic dysfunction. Acute resistance exercise appears to decrease parasympathetic activity regardless of age. This review examines the acute and chronic effects of resistance exercise on HRV in young and older adults.